O excesso de prazo na prisão preventiva e a razoável duração do processo - Araújo, Kayque Costa (2017)
The objective of this study is to analyze pretrial detention by observing constitutional and criminal procedural principles regarding its duration, as well as seeking to understand the criteria, or lack thereof, in relation to the decisions that keep the defendants imprisoned even in cases where it is reasonable that the defendant can respond to the lawsuit in freedom. In addition, it will be analyzed the moment in which the defendant is in preventive custody for a period of time superior to the necessary one so that the process instruction is finished, where the illegal embarrassment by the existence of excess of term in the prison of the individual is verified, the great problematic is that for lack of laws that govern this term, individuals depend on the interpretation of magistrates about the existence or not of the excess of term, often making the defendant await their judgment imprisoned for an unreasonable and disproportionate period of time.